Substituiç\~ao de poupança interna por externa e sobreapreciaç\~oes da taxa de câmbio - Marcos Rocha; Nelson Marconi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper evaluates the strategy of growth cum foreign savings adopted by many emerging countries, and its consequences. Bresser-Pereira and Nakano (2003) points out that there is in emerging countries a high rate of substitution of foreign and domestic savings during the process of influx of foreign capitals as a result from a dependent growth policy. This savings displacement happens because most of the resulting deficit in current account (the foreign savings) turns into consumption of imports; the parcel used as investment expenditures is small, since these economies has a high propensity of consumption and also because this policy tends to over-evaluate the real exchange rate. The chapter evaluates theoretically and empirically the existence of savings displacement and the adverse role of the of the real exchange rate valuation. To this aim, it is estimated a System-GMM dynamic panel using a panel sample of 48 countries of medium income, in the period span of 1970-2004. The results show a significant process of substitution savings, allied to an interaction between overvaluation of the exchange rate and the influx of external financial flows.
Keywords: O11; O14; O24; F43; 330; exchange rate; international trade; emerging countries